mRNA-Mediated Duplexes Play Dual Roles in the Regulation of Bidirectional Ribosomal Frameshifting - Wan-Ping Huang (International Journal of Molecular Sciences, 2018)
In contrast to −1 programmed ribosomal frameshifting (PRF) stimulation by an RNA pseudoknot downstream of frameshifting sites, a refolding upstream RNA hairpin juxtaposing the frameshifting sites attenuates −1 PRF in human cells and stimulates +1 frameshifting in yeast. This eukaryotic functional mimicry of the internal Shine-Dalgarno (SD) sequence-mediated duplex was confirmed directly in the 70S translation system, indicating that both frameshifting regulation activities of upstream hairpin are conserved between 70S and 80S ribosomes. Unexpectedly, a downstream pseudoknot also possessed two opposing hungry codon-mediated frameshifting regulation activities: attenuation of +1 frameshifting and stimulation of a non-canonical −1 frameshifting within the +1 frameshift-prone CUUUGA frameshifting site in the absence of release factor 2 (RF2) in vitro. However, the −1 frameshifting activity of the downstream pseudoknot is not coupled with its +1 frameshifting attenuation ability. Similarly, the +1 frameshifting activity of the upstream hairpin is not required for its −1 frameshifting attenuation function Thus, each of the mRNA duplexes flanking the two ends of a ribosomal mRNA-binding channel possesses two functions in bi-directional ribosomal frameshifting regulation: frameshifting stimulation and counteracting the frameshifting activity of each other.